2017
DOI: 10.3389/fphys.2017.00830
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophy Stimulation at the Onset of Type I Diabetes Maintains the Soleus but Not the EDL Muscle Mass in Wistar Rats

Abstract: Diabetes mellitus induces a reduction in skeletal muscle mass and strength. Strength training is prescribed as part of treatment since it improves glycemic control and promotes increase of skeletal muscle mass. The mechanisms involved in overload-induced muscle hypertrophy elicited at the establishment of the type I diabetic state was investigated in Wistar rats. The purpose was to examine whether the overload-induced hypertrophy can counteract the hypotrophy associated to the diabetic state. The experiments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 91 publications
(126 reference statements)
2
16
0
1
Order By: Relevance
“…Low-expressed WNT7A was detected in GDM mice, and the further down-regulation of WNT7A contributed to deteriorating insulin resistance and hepatic gluconeogenesis in GDM mice. Partly in line with our findings, the diminished WNT7A expression has been validated in streptozotocin-induced diabetic rats [ 43 ]. In streptozotocin-induced type 2 diabetic rats, Wang et al .…”
Section: Discussionsupporting
confidence: 90%
“…Low-expressed WNT7A was detected in GDM mice, and the further down-regulation of WNT7A contributed to deteriorating insulin resistance and hepatic gluconeogenesis in GDM mice. Partly in line with our findings, the diminished WNT7A expression has been validated in streptozotocin-induced diabetic rats [ 43 ]. In streptozotocin-induced type 2 diabetic rats, Wang et al .…”
Section: Discussionsupporting
confidence: 90%
“…A fast muscle is mainly composed of type 2 fibers, while a slow muscle is composed of type 1 fibers. The experimental method was as described by Shilveira and Fortes [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, many of these patients presented with reduced muscle function, involving lower SMI and limb muscle strength. The influence of type 1 diabetes on skeletal muscle mass has been analyzed in humans and rodent's models [16,17]. These results clearly showed that type 1 diabetes was associated with impaired skeletal muscle mass and strength.…”
Section: Sarcopenia and Diabetesmentioning
confidence: 98%